L’intelligence économique en faveur de la dynamique entrepreneuriale par les pôles économique intelligents Étude exploratoire a l’entreprise sonatrach aval - Dr. HAID , Zahia (Finance and Business Economies Review, 2018)
In a difficult economic context caused by Low oil prices. The Algerian government has adopted a new economic approach centered on local development. Thus, by putting forward a new mode of participative management allowing triggering an entrepreneurial dynamic through the creation of economic poles. The results we have achieved show that economic intelligence represents a promising alternative for the Algerian government, to instil the momentum of productive investment, by stimulating entrepreneurial actions, through an interconnection between all actors economies in the domain of enterprises creation and support.